Influence of Conductive Pollution on Eddy Current Sensor Signals, ISSn / e-ISSN 1061-8309 / 1608-3385 - Abdou Abdelhak; Bouchala Tarek; Nabil Benhadda; Bachir Abdelhadi; Benoudjit Azeddine (Russian Journal of Nondestructive Testing, 2018)
This paper presents a study of a surface crack detection in which the volume is filled by conductive substances due to the polluting environment. Hence, this investigation demonstrates by numerical simulation that electric conductivity is a crucial property that has to be added to the other defect geometrical characteristics in order to complete the developed models. Consequently, introducing the tolerance in percent in the measured impedance is necessary in some conditions. So, the obtained results demonstrate that the signal amplitude passes from 0 to 78% of the maximal amplitude when the defect conductivity rises from 0 to 0.5 Ms/m. On the other hand, the relative difference of the resistance partincreases according to defect volume. For example, for a defect of 0.3 MS/m, the relative difference of the resistance varies from 52 to 62% of the maximal amplitude when the defect depth varies from 0.5 to 2.25 mm. These results can be exploited to show the effect of the conductive substances occupying the crack volume. In fact, the controller using EC-NDT technique must take into consideration the presence of conductive polluting elements in the crack volume. So, this condition becomes primordial and necessary according to the degree and nature of pollution.